2014
DOI: 10.1016/j.gaceta.2014.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Desigualdades en la salud autopercibida de la población española mayor de 65 años

Abstract: This review shows that, among older people, inequalities in self-perceived health due to socioeconomic status and gender have persisted in time. Future research is needed to cast light on the factors determining the persistence of these inequalities among older people, so that specific health policies can be designed for this sector of the population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 46 publications
(64 reference statements)
1
7
0
5
Order By: Relevance
“…The dependent variable was self-perceived health, as recorded in the SLC under “General health status”. Self-perceived health provides a multidimensional approach to health [ 50 52 ]; and is a good predictor of mortality [ 53 , 54 ], morbidity [ 55 ], disability, and use of health services [ 56 58 ]. For the purposes of our research, self-perceived health was collapsed as a dichotomous variable: good self-perceived health (very good or good) and bad self-perceived health (fair, bad, or very bad).…”
Section: Methodsmentioning
confidence: 99%
“…The dependent variable was self-perceived health, as recorded in the SLC under “General health status”. Self-perceived health provides a multidimensional approach to health [ 50 52 ]; and is a good predictor of mortality [ 53 , 54 ], morbidity [ 55 ], disability, and use of health services [ 56 58 ]. For the purposes of our research, self-perceived health was collapsed as a dichotomous variable: good self-perceived health (very good or good) and bad self-perceived health (fair, bad, or very bad).…”
Section: Methodsmentioning
confidence: 99%
“…In some studies, no association was found between SRH and health factors such as hospital morbidity, occupational accidents and consumption of medicines among the Spanish general population [27]. However, more recent studies in the general Spanish population have demonstrated the relationship between objective health and SRH [28, 29], physical disability [30], functional performance, physical and social activity [31] or mental health [32]. Since the relationship between SRH and mortality has been demonstrated [33], its use in national and international surveys has increased and SRH has been recommended as a useful and convenient tool in national surveys over recent decades [34].…”
Section: Introductionmentioning
confidence: 99%
“…La autopercepción de salud es una medida determinada por múltiples factores. Si bien en la literatura científica se encuentran estudios que muestran su relación con indicadores como morbilidad, mortalidad, consumo de medicamentos, accidentabilidad laboral, utilización de servicios sanitarios, salud mental o capacidad funcional, entre otros6, 7, 8, es de especial interés la relación que encuentran algunos autores entre la salud percibida y los estilos de vida9, 10, 11, 12, 13, 14, 15, 16, incluyendo los hábitos alimentarios, ya que se ha comprobado que, en general, los estilos de vida repercuten favorablemente en el estado de bienestar.…”
Section: Introductionunclassified